Simple approach to group theory in chemistry - Swarnalakshmi, S.; Saroja, T; Ezhilarasi, R M (Hyderabad: University Press, 2008)
he book explains: The basics of Group Theory. What symmetry elements and operations are? How to identify point groups? The theorems involved and the applications of Group Theory to spectroscopy. This book has been specially designed to use a simple and easily understandable approach that explains the basics of symmetry elements and operations, how to identify point groups and the application of group theory in spectroscopy. The numerous worked-out examples and illustrations of symmetry elements and operations guide the reader in a step-wise manner through the subject. Even those without a background in mathematics will find this approach easy and helpful. The book is based on the prescribed syllabus for M Sc Chemistry and can be used by students across India as a textbook. It can be used as a reference book by B.Sc Chemistry students.
Appendices I-II, 126-140p.; References 141-145p.; Index 146-147p.
Keywords: Chemistry; Group theory